Thoughts on the Postpartum Situation - Scuro, Jennifer (Frontiers in Sociology, 2018)
The event of childbirth carries with it a dominant narrative: that a pregnant woman happily gives birth to a baby. This appears to be quite a simple formulation—as if a natural fact, as if plain and common sense. Yet, the complexities masked by the mythological and whitewashed quality of this narrative, as I have already argued recently in The Pregnancy ≠ Childbearing Project: A Phenomenology of Miscarriage (Feb 2017), harms and even kills women. In this paper, I expand on the problem of what I term “dismemberment after birth” as it operates invisibly in the “postpartum situation.” The dominant narrative, combined with a pervasive cultural misogynoir— manifesting specifically as an antagonism toward black women and women of color—as medicalized and ableist establishment of care, renders women without resource if they cannot maintain the desires and embodiments required of a contented and successful maternity. The naturalized assumptions about the narrative move from the birth event to “having a baby” are disrupted here with hope of opening up an opportunity to validate and diversify the more non-linear narratives. As an afterthought to these disruptions, I offer an additional challenge to anti-natalist thinking in its limited insight into the postpartum situation.